EVALUATION OF PROTECTIVE EFFECT OF CURCUMIN AGAINST CYCLOPHOSPHAMIDEINDUCED COGNITIVE IMPAIRMENT IN SWISS ALBINO MICE - ASHUTOSH KUMAR YADAV; HARINATH DWIVEDI; DHARAMVEER (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The objective of present study was to evaluate the effect of curcumin against cognitive dysfunctions associated with chemotherapeutic agent cyclophosphamide in swiss albino mice. Methods: The symptoms of chemobrain in Swiss mice were observed by the administration of cyclophosphamide 50 mg/kg body wt. intraperitoneally once daily for three weeks. Oral treatment of test drug curcumin at dose 200 and 400 mg/kg body wt. was administered daily for 3 weeks. Donepezil was used as standard drug at 3mg/kg body wt. orally. Assessment of memory dysfunction was done by morris water maze, passive avoidance test and elevated plus maze test. Anti-oxidant parameters were also checked from the isolated brain samples. Results: It was found that the cyclophosphamide reduced the cognitive ability in Swiss albino mice based on behavioural and anti-oxidant parameters whereas the animals treated with curcumin were significantly protected from behavioural cognitive abnormalities. The anti-oxidant parameters of brain also support the behavioural findings. Conclusion: The data obtained from this study proved that the curcumin is having the ability to protect the cyclophosphamide induced cognitive dysfunction and could be the promising treatment strategies to protect the chemobrain.